Analisis Implementasi PSAK No. 109 Pada Lembaga Amil Zakat (Rumah Zakat Indonesia) - HAKIM B51108025, DESRA ARIADI (Jurnal KIAFE, 2015)
Zakatisone ofthe threepillars of Islam, the charitycanhelp easethe burdens of others, especiallythe poor. It is necessary forthe proper managementandtrust. The purposeof thisstudywas to determine thereportingandmanagementapplicationzakat, donation andcharityat the Institute ofZakat(Rumah Zakat Indonesia) in accordancewithPSAK109anddetermine the factorsthatmakePSAK109can"™t beapplied. This research is aqualitativedescriptivemethod. Methods ofdata collectionin the form ofprimary dataandsecondary data, by means ofinterviewsandobservations. The analytical toolusedinthis studyarePSAK109.The data inthisstudyisto analyzethe application ofPSAK109onthe InstituteZakat(Rumah Zakat Indonesia). There arefouraspectson which theanalyzesof PSAK109, namely: the recognition, measurement, presentation and disclosure. In the aspect ofpresentingthe annualreportusing theRumah Zakat Indonesiain the formof datareceptionanddistribution ofzakat, donation andcharity. Froma fewparagraphsinPSAK109, RumahZakatIndonesia has notfullyadopted PSAK109is. This is due tothe lack ofacceptance ofcharity, donation andcharityin the form ofnon-cash. Keywords ; OPZ Practiced Accounting, Zakah Accounting, Religious Accounting, Applied Fund Accounting